Regional odontodysplasia in maxillary right anterior region–First report: Clinical management in relation to 2 case reports. Issue 2 (August 2020) - Ide, Masamichi; Oshima, Yohei; Chiba, Toshie; Adaniya, Akari; Kuroki, Takako; Asada, Yoshinobu
Abstract: Regional odontodysplasia is a rare developmental anomaly usually affecting maxillary anterior region. Enamel and dentine of the affected teeth are severely hypoplastic and the radiographs of the affected teeth show a ghostly appearance. The aim of this study was to report the clinical management of two girls with odontodysplasia. All of the affected primary teeth could not maintain; therefore, they were extracted followed by application of a removable space maintainer. As successor permanent teeth of the affected primary teeth were also severely hypoplastic, it is important that development and eruption of the successor permanent teeth be continued to observe periodically.